Metode Permainan Berbantuan Bingo Edukasi dalam Mewujudkan Pembelajaran Bermakna pada Mata Pelajaran Pendidikan Pancasila - Eka Widiarti, Anisah; Kurnisar (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to determine the effect of implementing game-based learning methods on the realization of meaningful learning in Pancasila Education at SMAN 1 Martapura. The research employed a quantitative approach with a quasi-experimental method, specifically the non-equivalent group design. The population consisted of 358 tenth-grade students, with samples selected through purposive sampling. Class XC was designated as the experimental group, receiving treatment using the